UNIVERSITY STUDENTS ACCEPTANCE OF INTEGRITY AND ANTI-CORRUPTION TOPICS INCORPORATED WITHIN LANGUAGES AND HUMANITIES COURSES VIA CONTENT BASED INSTRUCTION APPROACH - Mohd Mohamed Zin; Norkhairi Ahmad; Mohd Adri Mohd Din; Adifarizal Mohd Ariffin (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2023)
The objective of the study is to measure the university student; acceptance of the Content based instruction (CBI) approach for The Integrity and Anti-Corruption (IAC) and their understanding on corruption and integrity issues in Malaysia as a whole. This is important as the battle  against corruption must be carried out via all means. Thus the CBI approach enables lecturers to emphasize IAC within their existing languages and humanities courses. Data was elicited via survey questionnaires and selective interviews  on 90 students who enrolled in the various  courses for February semester. The findings show that majority of the respondents were very receptive to the integration of IAC topics via CBI in the languages and humanities courses and they  have good understanding on the main aspects of integrity and  corruption. However some of the students  perception on a few micro practices relating to corruption shows somewhat worrying results. Suggestions are put forth to improve the content integration in the courses so that the learning outcomes will be better achieved as  the understanding of IAC  reach a better level.